2017
DOI: 10.3889/oamjms.2017.102
|View full text |Cite
|
Sign up to set email alerts
|

The Outcome of Assisted Reproductive Techniques among Couples with Male Factors at Prince Khalid Bin Sultan Fertility Centre, Kingdom of Saudi Arabia

Abstract: BACKGROUND:Thirty-three percent of infertility due to paternal factors, there are an increasing proportion of couples who decide to conceive by assisted reproductive techniques (ART). The outcome prediction is pivotal for decision making.AIM:We aimed to study the pregnancy outcomes of different ART with male factors infertility.METHODS:This is retrospective cross-sectional study conducted at Tabuk, Kingdom of Saudi Arabia. One hundred fifteen patients’ records reviewed using a structured checklist to collect d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Insight into the literature on male infertility and its causes in Saudi Arabia, very few studies were reported from this region. Mukhtar and his group (2017) found that about half million couples require assisted conception ( Mukhtar et al, 2017 ). Male factor infertility (72%) was accountable for increased rate of infertility among infertile couples ( Alasmari et al, 2018 , Alosaimi et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Insight into the literature on male infertility and its causes in Saudi Arabia, very few studies were reported from this region. Mukhtar and his group (2017) found that about half million couples require assisted conception ( Mukhtar et al, 2017 ). Male factor infertility (72%) was accountable for increased rate of infertility among infertile couples ( Alasmari et al, 2018 , Alosaimi et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Especially, studies on the incidence and the causes of male infertility and reproductive disorders are hardly available. Limited information available reveals that infertility is a serious problem with an incidence of 19% (Al‐Turki, ) and about half million couples are needing help with ART (Mukhtar, Shaman, Mirghani, & Almasalmah, ). Alarmingly, in a recent study on 2,317 infertile couples, 72% of problem was attributed to male factor infertility (Alasmari et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Cases with male-associated infertility factors were grouped into two categories: spermatic diseases (19%) and testicular diseases (14%). Women with male-associated infertility factors had the highest pregnancy rate using in vitro fertilization [ 29 ].…”
Section: Discussionmentioning
confidence: 99%